Sadness and consumption - Garg, Nitika; Lerner, Jennifer S. (Journal of Consumer Psychology, 2013)
AbstractSadness influences consumption, leading individuals to pay more to acquire new goods and to eat more unhealthy food than they would otherwise. These undesirable consumption effects of sadness can occur without awareness, thus representing more than just conscious attempts at “retail therapy.” In an experiment with real food consumption, the present paper examines the hypothesis that sadness' impact on consumption could be attenuated if the choice context counteracted appraisals of helplessness and enhanced a sense of individual control. Results revealed that: (1) sadness elevates self‐reports of helplessness in response to the emotion‐inducing situation, (2) helplessness mediates the sadness–consumption effect, and (3) inducing a sense of control (via choice) attenuates sadness' effect.